New Strait Times , 18 April 2009 - Sheridan Mahavera; Siti Nurbaiyah Nadzmi (The New Straits Times Press (M) Bhd, 2009)
Following our package last week on what's being taught as history in the nation's schools, Sheridan Mahavera and Siti Nurbaiyah Nadzmi listeb to what historians and teachers have to say.